2014
DOI: 10.1037/a0037080
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation in the “making”: Lingering mood repair in textile handcrafters.

Abstract: A variety of activities can help people improve their bad moods. We propose activities that are engaging, arousing, and associated with the mental state of flow can be particularly helpful and inspire what we call rejuvenation. Rejuvenation, as we conceive it, is a state of feeling restored, renewed, and ready to start anew, which continues beyond immediate participation in a mood-repair activity. To explore this model, we examined rejuvenation in a sample of 435 women, all experienced in some form of textile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Interestingly, Feldman Barrett and Russell (1999) have suggested that the dimensions of mood valence and arousal should not be combined, nor should one be emphasized over the other. Consistent with Kuppens et al (2013), Collier and colleagues have reported that high positive mood and high arousal occur together during art-making and crafting (Collier and von Károlyi 2014;Collier et al 2016;Collier and Wayment 2018). Possibly, Maker and DIY activities lend themselves towards enhancing both positive mood and arousal levels, which may help explain the association with increased SWB during Maker activities.…”
Section: Arousal and Positive Mood During Diymentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, Feldman Barrett and Russell (1999) have suggested that the dimensions of mood valence and arousal should not be combined, nor should one be emphasized over the other. Consistent with Kuppens et al (2013), Collier and colleagues have reported that high positive mood and high arousal occur together during art-making and crafting (Collier and von Károlyi 2014;Collier et al 2016;Collier and Wayment 2018). Possibly, Maker and DIY activities lend themselves towards enhancing both positive mood and arousal levels, which may help explain the association with increased SWB during Maker activities.…”
Section: Arousal and Positive Mood During Diymentioning
confidence: 87%
“…Flow has been associated with many benefits, including overall happiness and well-being (e.g., Collins et al 2009;Griffiths 2008;Rogatko 2009;Sahoo and Sahu 2009) as well as increased healthrelated quality of life (Hirao et al 2012) and decreased depression (Mosing et al 2018). Engagement, a component of flow, has also been reported as a critical factor that contributes to longer-lasting mood-repair and SWB during maker activities (Collier 2011;Collier and von Károlyi 2014;Collier et al 2016;Collier and Wayment 2018). High engagement and flow during DIY could then lead to greater productivity and success with DIY, which would further enhance SWB.…”
Section: Flow and Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research needs to test whether these emotion-creativity links will be similar in adult or older adult community samples or among working adults expressing creativity at higher levels in their professions ("Pro-c" creativity; Kaufman & Beghetto, 2009). We suspect that patterns will be similar for other forms of "little c" creativity regardless of age given biographical and interview data from older populations showing a link between creativity and high activation and engaged states (e.g., Collier & von Károlyi, 2014). However, we cannot say whether creativity expressed at higher levels of mastery ("Pro-c" or "Big C") would function similarly (Kaufman & Beghetto, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Collier and von Karolyi (2014) were interested in seeing if working with textiles could be a way to alter a negative mood long-term, rather than just in the moment. They used the term rejuvenation, and specifically textile rejuvenation, to identify improved mood that continued after participation in textile work (Collier & von Karolyi, 2014, p. 1).…”
Section: Textile Work In Art Therapymentioning
confidence: 99%